Isolasi dan Karakterisasi Flavonoid dari Beras Ketan Hitam (Oryza Sativa L. Var Glutinosa) - Sri Benti Etika; Iryani Iryani (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
This study aims to isolate and characterize the isolated flavonoid compounds from glutinous rice (Oryza Sativa L. Var Glutinosa). The method that used was maserasi with methanol solvent, multilevel fractionation with n-hexane and ethyl acetate. The separation of chemical components using column chromatography and tested its purity by melting point test and TLC. Characterization of isolated flavonoids using color reagents (H2SO4, NaOH, Mg-HCl), KKt-2A, UV-Vis and FT-IR. The powder (amorphous) flavonoid isolation results have a melting point of 236.5-237.8 oC. Flavonoid powder added H2SO4 produces a yellow color, with NaOH producing a violet color, and Mg-HCl produces a red color. KKt-2A with a BAA developer has Rf 0.49 and 15% acetic acid having Rf 0.09. The UV-Vis spectrum shows maximum absorption at 532 nm wavelength. The results of powder analysis (amorphous) flavonoid using FT-IR showed absorption at wave number 3.330,40 cm-1, 2838,96 cm-1, 1,656,23 cm-1, 1,421,85 cm-1, 1,112,25 cm-1, 1,019,27 cm-1 and 697,76 cm-1. According to those data it can be concluded that flavonoids that isolated have the form of powder (amorphous) which belong to anthocyanin group that have o-diOH on ring B and have a conjugated double bond.Keywords- Black Sticky Rice, Flavonoid, Fractionation, FT-IR, Maserasi, UV-Vis.